ASSESSING THE USE OF LAW LIBRARY COLLECTIONS AMONG FINAL-YEAR LAW STUDENTS OF USMANU DANFODIYO UNIVERSITY, SOKOTO STATE, NIGERIA - ABDULLAHI, KASIM; FAKANDU , ALI MUHAMMED (Sokoto Educational Review, 2025)
This study assessed the use of law library collections among the final-year law students of Usmanu Danfodiyo University, Sokoto State, Nigeria. The research objectives among others include: to assess the purpose of using the law library by final year students, to determine the availability of law library collection and to identify the challenges faced by the final year law students in unitizing the law library collection. The research design of the study was descriptive survey and the population of the study comprises one hundred and twenty-three (123) law students of 2018/2019 academic session. Questionnaire was used as the instrument for data collection. The findings revealed that law students used law library mostly for writing projects than reading, writing assignment, supplement lectures note writing project among others. The study revealed that law reports is the most available information in the law library compared to others such text books, journals, electronic resources and database. The study revealed that lack of standby generator is the major challenge faced by the final year law students in utilizing the law library collection. It was concluded that the final year law students used the library mostly for the purpose of writing projects. Despite the benefits of these library collections, the law library faced numerous challenges but lack of standby generator is the major challenge in the law library among the final-year students. The study recommends that, the law library should encourage the final year students to utilize other information resources such textbooks, reference materials, databases, among others. The faculty and law library should acquire more information resources and provided power back up in the library for effective service delivery.